تحليل السياسات العامة: قضايا نظرية واشكاليات منهجية - العلوي أ. أمل أبو القاسم (Aljameai)
مستخلص: هذا البحث غايته التعريف بعملية تحليل السياسات العامة واستعراض جوانبها وتوجهاتها الفكرية وتخلص إلى الصعوبات والإشكاليات التي تواجه هذه العملية، باعتبار هذه العملية تمثل ما يسمى "الحلقة المفقودة" في دراسات السياسات العامة. اعتمد البحث على المنهج التحليلي واستخدام الأسلوب المكتبي وما يوفره من بيانات ومعلومات تتعلق بموضوع الدراسة. وخلص إلى جملة من التوصيات المهمة التي من شأن الدفع بدراسات تحليل السياسة العامة في ليبيا ومؤسساتها العلمية ومراكزها البحثية. Abstract: This study sought to review the different aspects of the process of public policy analysis in terms of its concept, importance, objectives, levels, stages and procedural steps, as well as schools of thought that dealt with the interpretation of the process of analyzing these policies according to different intellectual and theoretical frameworks. The paper also reviewed the tools and methodologies of public policy analysis and the difficulties facing the process of public policy analysis, both on the theoretical and practical side. The analytical method was relied on, as was the office method and the data and information it provides related to the subject of the study. This study raised research questions and tried to answer them, and these questions are what is meant by the process of analyzing public policies and its nature? What are the most prominent theories and schools of thought prevailing in Libya and its scientific institutions and research centers, the study reached the most important results that the process of analyzing public policies is a complex process as a result of the overlap and intertwining of variables, which is a process of a scientific, technical and professional nature. The process of policy analysis also faces many difficulties because it is not characterized by continuity, permanence and stability, in addition to the overlap of national, local and regional levels in the field of theory for public policy analysis. What are the problems and difficulties facing the process of policy analysis? It concluded with a number of important recommendations that will advance public and international policy analysis studies.